Lipokathexis: A fat paradox - Sanjay Kalra; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2022)
’Lipokathexis’ is derived from the term ’Lipo’ meaning fat and ’kathexis’ which means retention. We propose this name for describing a clinical situation wherein despite excessive stores of fat are noted in the body but lower levels of circulating lipids are present in the blood. Different disease conditions that express such a phenotype including Tangier’s disease, metabolic healthy obesity and those coming under the domain of obesity paradox have been described in this manuscript. This paper will invoke the readers interest on different facets of lipid metabolism in context of metabolic medicine and explore this concept of "Fat Paradox". Keywords: Cholesterol, dyslipidemia, hyperlipidemia, LDL cholesterol, myelokathexis, Tangier’s disease.